2001
DOI: 10.1002/app.1831
|View full text |Cite
|
Sign up to set email alerts
|

Large deformation mechanical behavior of gelatin–maltodextrin composite gels

Abstract: ABSTRACT:The large deformation failure behavior of gelatin-maltodextrin composite gels was assessed. All the studied compositions were selected to lie within the incompatibility domain of the gelatin-maltodextrin phase diagram at 60°C, which produced gelatin continuous (maltodextrin included) and maltodextrin continuous (gelatin included) composites. Composite microstructural evaluation was performed using confocal laser scanning microscopy (CLSM). The large deformation mechanical behavior was measured in tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Gelation is seen to precede the large increase in turbidity, clearly showing that the demixing process leading to the formation of micron size domains occurs in the gel state. This is a rather unexpected finding, as in most biopolymer mixtures, gelation usually traps phase separation by freezing fluctuations of concentration 35, 52, 53…”
Section: Discussionmentioning
confidence: 90%
“…Gelation is seen to precede the large increase in turbidity, clearly showing that the demixing process leading to the formation of micron size domains occurs in the gel state. This is a rather unexpected finding, as in most biopolymer mixtures, gelation usually traps phase separation by freezing fluctuations of concentration 35, 52, 53…”
Section: Discussionmentioning
confidence: 90%
“…Some investigations have shown that the concentration of maltodextrin above 20% resulted in the formation of stronger gels [ 34 , 35 ]. The gelatin-maltodextrin composite gels exhibited a brittle failure behaviour which occurred at a lower strain than observed for the gelatin gels [ 36 ]. The presence of nuclei (aggregates of double helices of amylose) in maltodextrin gels created larger number of crystallites, which led to the rapid formation of a stronger gel.…”
Section: Resultsmentioning
confidence: 99%
“…When included in a mixed gel system, unique fat-like properties have been observed (Chronakis, 1998). Surrounding this effect, many studies have focused on maltodextrin mixed gels with gelatin (Brown, Foster, Norton, & Underdown, 1995;Butler & Heppenstall-Butler, 2003;Kasapis, Morris, Norton, & Brown, 1993;Kasapis, Morris, Norton, & Clark, 1993b;Lorn & Hermansson, 2000;Lundin et al, 2000;Nickerson et al, 2006;Normand, Plucknett, Pomfret, Ferdinando, & Norton, 2001), pectin (Picout, Richardson, & Morris, 2000), and agarose (Loret, Frith, & Fryer, 2006). Several patents have even been granted utilizing the unique creaminess of maltodextrin-gelatin mixed gel system for reduced fat food products (Cain et al, 1990;Wesdorp, Madsen, Norton, & Brown, 1995).…”
Section: Introductionmentioning
confidence: 99%